2014
DOI: 10.1590/s0100-204x2014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative demography of the exotic Harmonia axyridis with other aphidophagous coccinellids reared on artificial diet

Abstract: -The objective of this work was to compare biological aspects and life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
5
1
4
Order By: Relevance
“…Short-lived coccinellids reproduce uniformly (almost constantly) during their lifetime, as observed for C. sanguinea (Figure 1). Milléo et al (2014) also reported an almost constant oviposition rate for C. sanguinea fed on E. kuehniella eggs. In contrast, long-lived females show a significant and rapid increase in reproductive activity, followed by progressive lessening, a characteristic shown by H. axyridis and H. convergens, in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Short-lived coccinellids reproduce uniformly (almost constantly) during their lifetime, as observed for C. sanguinea (Figure 1). Milléo et al (2014) also reported an almost constant oviposition rate for C. sanguinea fed on E. kuehniella eggs. In contrast, long-lived females show a significant and rapid increase in reproductive activity, followed by progressive lessening, a characteristic shown by H. axyridis and H. convergens, in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Sin embargo, estos resultados difieren con lo reportado por Solano et al (2016), quienes obtuvieron una pre-oviposición promedio de 6,0 ± 1,1 días para C. sanguinea sobre A. craccivora en las mismas condiciones de temperatura. Por otra parte, Milléo et al (2014) indicaron una pre-oviposición de 24,30 ± 1,36, 9,50 ± 0,42 y 12,20 ± 8,89 días para las especies C. sanguinea, Harmonia axyridis Pallas y H. convergens, respectivamente, alimentadas con Anagasta kuehniella Zeller. Zhao et al (2015) registraron un periodo de pre-oviposición de 8,8 ± 0,3 días para el coc-cinélido Cheilomenes sexmaculata Fabricius sobre M. persicae; mientras que Ghanim et al (2014) reportaron un promedio de 4,0 a 5,0 y 5,0 a 5,5 días de pre-oviposición en hembras de Coccinella undecimpunctata Linnaeus alimentadas con Sitobion avenae Fabricius y S. graminum, respectivamente.…”
Section: Fecundidad Y Tasa De Oviposición De C Sanguineaunclassified
“…Este comportamiento refleja una curva de tipo I, en donde la mortalidad se concentra principalmente en los individuos de edades avanzadas (Rabinovich, 1980). Estos resultados coinciden con los registrados por Milléo et al (2014) y Solano et al (2016) quienes encontraron una curva de tipo I para C. sanguinea alimentado con huevos de A. kuehniella y ninfas de A. craccivora, respectivamente, en las mismas condiciones de temperatura evaluadas en este estudio. Por otra parte, diversos autores registraron un comportamiento similar en otras especies de coccinélidos como Cryptolaemus montrouzieri Mulsant, Coccinella septempunctata L., Ceratomegilla undecimnotata Schneider, Propylea quatuordecimpunctata L., E. connexa, H. axyridis y Exochomus marginipennis LeConte (Torres y Marcano, 2007;Kontodimas et al, 2008;Duarte y Zenner, 2009;Ali y Rizvi, 2010;Castro et al, 2011;Palomares et al, 2016).…”
Section: Tabla De Vida De C Sanguineaunclassified
“…Além disso, a duração da fase pupal evidenciada para C. sanguinea nessa pesquisa, se equipara à verificada por Milléo;Godoy (2014) fornecendo ovos da traça a esta espécie comparada à outras espécies de joaninhas. O alimento da presa pode refletir nos parâmetros biológicos de C. sanguinea, como foi observado por Funichello et al (2012) alimentando a joaninha com pulgões criados em duas cultivares de algodão.…”
Section: Biometria Da Fase Larvalunclassified
“…Larvas da traça foram alimentadas com dieta à base de farinha de milho, farinha de trigo e lêvedo de cerveja até obtenção de adultos (LIMA FILHO;FAVERO;LIMA, 2001). Os ovos obtidos da traça foram inviabilizados e conservados em refrigerador, congelados a 5 ºC, para posteriormente serem oferecidos às larvas da joaninha seguindo a metodologia de Milléo;Godoy (2014).…”
Section: Introductionunclassified